The Capacity of Local Governments in Europe - Kuhlmann, Sabine. author. aut Link
XI, 121 p. 20 illus., 6 illus. in color.
Keywords: This book compares local self-government in Europe. It examines local institutional structures, autonomy, and capacities in six selected countries - France, Italy, Sweden, Hungary, Poland, and the United Kingdom - each of which represents a typical model of European local government. Within Europe, an overall trend towards more local government capacities and autonomy can be identified, but there are also some counter tendencies to this trend and major differences regarding local politico-administrative settings, functional responsibilities, and resources. The book demonstrates that a certain degree of local financial autonomy and fiscal discretion is necessary for effective service provision. Furthermore, a robust local organization, viable territorial structures, a professional public service, strong local leadership, and well-functioning tools of democratic participation are key aspects for local governments to effectively fulfill their tasks and ensure political accountability. The book will appeal to students and scholars of Public Administration and Public Management, as well as practitioners and policy-makers at different levels of government, in public enterprises, and in NGOs. Sabine Kuhlmann is Professor of Political Science, Public Administration and Organization at the University of Potsdam, Germany. Benoît Paul Dumas is Research Associate at the Chair for Political Science, Public Administration and Organization at the University of Potsdam, Germany. Moritz Heuberger is Research Associate at the Chair for Political Science, Public Administration and Organization at the University of Potsdam, Germany. .